A biomechanical comparison between locked 3.5-mm plates and 4.5-mm plates for the treatment of simple bicondylar tibial plateau fractures: is bigger necessarily better? - Hasan, Saqib (Springer International Publishing, 2013)
BACKGROUND: Evolution of periarticular implant technology has led to stiffer, more stable fixation constructs. However, as plate options increase, comparisons between different sized constructs have not been performed. The purpose of this study is to biomechanically assess any significant differences between 3.5- and 4.5-mm locked tibial plateau plates in a simple bicondylar fracture model. MATERIALS AND METHODS: A total of 24 synthetic composite bone models (12 Schatzker V and 12 Schatzker VI) specimens were tested. In each group, six specimens were fixed with a 3.5-mm locked proximal tibia plate and six specimens were fixed with a 4.5-mm locking plate. Testing measures included axial ramp loading to 500 N, cyclic loading to 10,000 cycles and axial load to failure. RESULTS: In the Schatzker V comparison model, there were no significant differences in inferior displacement or plastic deformation after 10, 100, 1,000 and 10,000 cycles. In regards to axial load, the 4.5-mm plate exhibited a significantly higher load to failure (P = 0.05). In the Schatzker VI comparison model, there were significant differences in inferior displacement or elastic deformation after 10, 100, 1,000, and 10,000 cycles. In regards to axial load, the 4.5-mm plate again exhibited a higher load to failure, but this was not statistically significant (P = 0.21). CONCLUSIONS: In the advent of technological advancement, periarticular locking plate technology has offered an invaluable option in treating bicondylar tibial plateau fractures. Comparing the biomechanical properties of 3.5- and 4.5-mm locking plates yielded no significant differences in cyclic loading, even in regards to elastic and plastic deformation. Not surprisingly, the 4.5-mm plate was more robust in axial load to failure, but only in the Schatzker V model. In our testing construct, overall, without significant differences, the smaller, lower-profile 3.5-mm plate seems to be a biomechanically sound option in the reconstruction of bicondylar plateau fractures.